ANALISIS KOMPARASI KINERJA PERBANKAN SYARIAH DAN PERBANKAN KONVENSIONAL - Dian Purnomo Jati; Karsidi Karsidi (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2012)
The purpose of this research is to compare between sharia banking performance and non-sharia banking performance in Indonesia. The tool of analysis include five components of financial ratios: (1) Capital Adequacy Ratio, (2) Non Performing Loan, (3) Return on Asset and Return on Equity, (4) Efficiency Ratio and (5) Loan to Deposit Ratio. This research use statistic tools of independent sample t-test. The result of this study are: (1) the study found the difference of Capital Adequacy Ratio between Sharia Banking and Non-Sharia Banking, (2) there is no difference about non performing loan between sharia banking and non-Sharia banking (3) there is no difference about ROA and ROE between sharia banking and non-Sharia banking, (4) there is no difference about efficiency ratio between sharia banking and non-Sharia banking, (5) there is no difference about loan to deposit ratio between sharia banking and non-Sharia banking and (6) there is no difference about total score of sharia banking performance and non-sharia banking performance. Although there is no significant difference, the total score of non-sharia banking performance is higher than sharia banking.